2020
DOI: 10.1108/ijesm-11-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Enforce environmental tax compliance model for the oil and gas industry

Abstract: Purpose It is basically known that the oil and gas industry contributes to various forms of pollution through air, acid rain and water, as well as different kinds of illnesses in humans and aquatic animals. Eventually, this adversely contributes to climate change owing to increases in emission levels in various stages of oil and gas operations ranging from extraction, refining, transportation and even consumption. Therefore, the purpose of this paper is to produce a simplistic model for compliance with environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Ukraine has an extremely low level of environmental taxation, which allows TPP owners to earn extra profits by deteriorating global ambient temperatures. As of January 1, 2019, the rate for emissions of 1 ton of CO 2 is only ₴10, which is €0.3, whereas it is estimated that at present 1 ton of CO 2 emissions causes damage in the global dimension of €30 (Mas’ud et al , 2020) and approximately at this level taxation of carbon emissions is set in the EU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ukraine has an extremely low level of environmental taxation, which allows TPP owners to earn extra profits by deteriorating global ambient temperatures. As of January 1, 2019, the rate for emissions of 1 ton of CO 2 is only ₴10, which is €0.3, whereas it is estimated that at present 1 ton of CO 2 emissions causes damage in the global dimension of €30 (Mas’ud et al , 2020) and approximately at this level taxation of carbon emissions is set in the EU.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of the importance of implementing environmental taxation coordinated with the energy business has been considered in a number of works. It was found that stable environmental taxation can have a positive effect on both the environment and economic development (Volchyn et al , 2013; Report Greenpeace, 2014; Mas'ud et al , 2020).…”
Section: Existing Review Of Literaturementioning
confidence: 99%
“…Evaluating the economic and social value from gas flaring is crucial for addressing environmental concerns and maximizing benefits (Romsom & McPhail, 2021). Environmental tax compliance models for the oil and gas industry aim to enhance regulatory frameworks and ensure adherence to environmental regulations (Mas'ud et al, 2020). Studies on environmental liabilities in the oil and gas industry stress the importance of life-cycle management and addressing climate change concerns (Zhao et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such compliance measures are tax audits and investigations after the taxpayers' file self-assessment returns. Despite recent developments in tax compliance research, which highlights the relevance of psychological variables, such as trust, deterrence measures are still relevant (Masud et al, 2020). Lois et al (2019) inferred that voluntary tax compliance is vital for governments to cope with budget deficits.…”
Section: Introductionmentioning
confidence: 99%